The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10600-011-9948-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitrobenzene oxidation of lignins from several plants of the family Gramineae

Abstract: It was found based on results from alkaline nitrobenzene oxidation of natural and isolated dioxane lignins from several plants of the family Gramineae such as rice husks, rice straw, and corn and sorghum stems that the studied lignins consisted of three types of structural units with the predominance of guaiacyl structures.Grasses (Gramineae Juss.) are distributed in nature on all continents, represent a significant part of the biomass of many biocommunities, and are considered one of the most widespread and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
2
1
0
Order By: Relevance
“…The GC-MS analysis of the nitrobenzene oxidation products showed that lignin in each organ consisted of guaiacyl, syringyl, and p-hydroxyphenyl units (Table 2), consistent with the result of thioacidolysis. The ratios of syringaldehyde to vanillin (S/V), which indicate the ratios of syringyl to guaiacyl lignins, were 0.61 in the inner part and 0.79 in the outer part (Table 2); the higher S/V ratio in the outer than the inner part was consistent with the results of the Mäule reaction (Figure 1D (Jung and Vogel 1992), and 0.37-0.59 in Miscanthus (Sarkanen and Hergert 1971)], and similar to those in small gramineous plants [e.g., 0.48-0.89 in rice straw (Dalimova and Abduazimov 1994;Dzhumanova and Dalimova 2011), and 0.72-0.93 in wheat straw (Dalimova and Abduazimov 1994)]. …”
Section: Lignin Structures Of E Arundinaceussupporting
confidence: 85%
“…The GC-MS analysis of the nitrobenzene oxidation products showed that lignin in each organ consisted of guaiacyl, syringyl, and p-hydroxyphenyl units (Table 2), consistent with the result of thioacidolysis. The ratios of syringaldehyde to vanillin (S/V), which indicate the ratios of syringyl to guaiacyl lignins, were 0.61 in the inner part and 0.79 in the outer part (Table 2); the higher S/V ratio in the outer than the inner part was consistent with the results of the Mäule reaction (Figure 1D (Jung and Vogel 1992), and 0.37-0.59 in Miscanthus (Sarkanen and Hergert 1971)], and similar to those in small gramineous plants [e.g., 0.48-0.89 in rice straw (Dalimova and Abduazimov 1994;Dzhumanova and Dalimova 2011), and 0.72-0.93 in wheat straw (Dalimova and Abduazimov 1994)]. …”
Section: Lignin Structures Of E Arundinaceussupporting
confidence: 85%
“…The GC-MS analysis of the nitrobenzene oxidation products showed that lignin in each organ consisted of guaiacyl, syringyl, and p-hydroxyphenyl units (Table 2), consistent with the result of thioacidolysis. e ratios of syringaldehyde to vanillin (S/V), which indicate the ratios of syringyl to guaiacyl lignins, were 0.61 in the inner part and 0.79 in the outer part (Table 2); the higher S/V ratio in the outer than the inner part was consistent with the results of the Mäule reaction (Figure 1D, E; Abduazimov 1994, Dzhumanova andDalimova 2011), and 0.72-0.93 in wheat straw (Dalimova and Abduazimov 1994)]. …”
Section: Lignin Structures Of E Ravennaesupporting
confidence: 77%
“…Alternatively, cellulolytic enzyme lignin (CEL) has commonly been used for the structural analysis of cell wall lignin, which utilizes cellulolytic enzyme hydrolysis prior to dioxane/water extraction of ball-milled wood meal to remove carbohydrates and achieve lignin with high yield and purity. , For decades, a lot of work was devoted to understanding the structural features of lignin from a plant cell wall; for example, the monomeric content of lignin polymer and some other structural features were analyzed with different chemical degradation methods such as alkaline nitrobenzene oxidation, ozonation, thioacidolysis, and derivatization followed by reductive cleavage that uses acetyl bromide for derivatization and zinc for reductive cleavage . These wet chemical methods can be very precise for specific functional groups and structural moieties.…”
Section: Introductionmentioning
confidence: 99%